Factors Influencing Students’ Understanding of Basic Statistical Concepts - Ismail, Nor Zatul-Iffa; Abu Kassim, Noor Lide; Mahmud, Zamalia (IIUM Journal of Educational Studies, 2022)
This study focused on modelling the influence of teaching practices, students’ attitudes towards statistics, learning practices and perceived ability on students’ understanding in basic statistical concepts using Structural Equation Modelling. A total of 416 students from four Malaysian public tertiary institutions made up the sample for this study. The results showed that students’ perceived ability in statistics has a strong influence on students’ understanding of basic statistical concepts (measured by performance) and students’ attitudes toward statistics. Teaching practices also significantly affect students’ learning practices. This study found that learning practices and teaching practices do not affect students’ attitudes toward statistics and do not lead to an increase in students’ understanding of basic statistical concepts as measured through their test performance.